2020
DOI: 10.1590/1983-21252020v33n313rc
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Bacterial Isolates for Sustainable Rice Blast Control

Abstract: Rice blast (Magnaporthe oryzae) limits rice (Oryza sativa) grain yields worldwide. The objective of this investigation was to morphologically, biochemically, and molecularly characterize six bacterial isolates, BRM 32109, BRM 32110, BRM 32111, BRM 32112, BRM 32113, and BRM 32114, and to determine their potential as antagonists to M. oryzae. Morphological characterization was based on colony formation and color, Gram staining, and fluorescent pigment production. Biochemical studies were based on cellulase, chit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
(32 reference statements)
0
9
0
2
Order By: Relevance
“…The Bacillus sp. BRM 32110 and S. marcescens BRM32113 species under study, were isolated from the rhizosphere of upland rice by Filippi et al (2011), who performed the phenotypic, biochemical and molecular characterization, through the ampli cation of the gene encoding the 16S rRNA region (Martins et al 2020). Other works of the same research group revealed that these same isolates are growth promoters in rice, soybean and bean crops, antagonists to some phytopathogens such as M. oryzae and B. oryzae and resistance inducers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Bacillus sp. BRM 32110 and S. marcescens BRM32113 species under study, were isolated from the rhizosphere of upland rice by Filippi et al (2011), who performed the phenotypic, biochemical and molecular characterization, through the ampli cation of the gene encoding the 16S rRNA region (Martins et al 2020). Other works of the same research group revealed that these same isolates are growth promoters in rice, soybean and bean crops, antagonists to some phytopathogens such as M. oryzae and B. oryzae and resistance inducers.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial isolate BRM32113 was initially identi ed by Martins et al (2020), as Burkholderia pyrrocinia, analyzing the sequencing obtained from the ampli cation of the 16S rRNA gene, and the biochemical and morphological identi cation. But the analysis of the 16S rRNA gene extract from the complete genome sequencing of isolate BRM 32113 revealed that it is from the genus Serratia and species marcescens.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mundialmente, o aumento da demanda por arroz se dá em função do crescimento constante da população. O consumo per capita global deste alimento é estimado em cerca de 57 kg/ano (NASCENTE et al, 2019) e estima-se que a demanda de arroz passará de 496 milhões de toneladas em 2020 para 555 milhões de toneladas em 2035 (MARTINS et al, 2020).…”
Section: Introductionunclassified
“…Dentre os estresses bióticos mais comuns que infectam a cultura de arroz, destaca-se a brusone. Causada por um fungo hemibiotrófico (Magnaporthe oryzae), a doença pode resultar em perdas de 100% em cultivares de arroz suscetíveis, limitando sua produtividade (MARTINS et al, 2020). De acordo com Jiang et al 2020, nas áreas tropicais e temperadas do planeta a brusone é avaliada como uma das doenças mais graves do arroz.…”
Section: Introductionunclassified